Analysis of solar cell parameters for efficient use of solar batteries for autonomous energy supply of country houses located in various regions of Russia - Korolev Ilya; Vasileva Natalya; Kravchenko Maxim; Fedorova Elena; Zavyalova Anna (E3S Web of Conferences)
The paper considers the parameters of solar cells for a country house with autonomous power supply from solar panels. An algorithm for determining the efficiency of solar panels is proposed. The conducted analysis of the distribution of solar radiation in Russia showed the most promising regions for the location of solar power plants for autonomous power supply of houses. The paper calculated the optimal angle of inclination of the solar module. Orientation of the receiving surfaces to a certain optimal angle to the horizon allows for maximum capture of incoming solar radiation. A practical experiment and calculation of the parameters of the solar module were conducted. An example of calculating solar panels to assess the generation of electrical energy and the payback of their use is considered.